DETERMINANTS OF FIRM VALUE FOR WHOLESALE SUB-SECTOR COMPANIES IN 2016-2019 WITH BEHAVIORAL ACCOUNTING APPROACH - Nicholas Renaldo; Andi Andi; Nuriman M. Nur; Achmad Tavip Junaedi; Harry Patuan Panjaitan (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
Stock returns which are decreasing every year are a problem for investors who want to get benefit from capital gains. The purpose of this study is to determine the factors that affect firm value. The sample in this study were 15 companies in the wholesale sub-sector. The sample selection method is purposive sampling with criteria listed on the Indonesia Stock Exchange in 2015-2019 and the data to be processed does not have outliers. The results showed that the PER and EPS had a significant effect on Stock Returns, while DER, Size, and Growth had no significant effect on Stock Returns. Recommendations that can be given for this research are that companies maintain consistent profits so that investors are still interested in investing, maintain capital structure, create stable equity growth and maintain company size so as not to be overvalued by investors and potential investors.